Field plus lab experiments help identify freezing tolerance and associated genes in subtropical evergreen broadleaf trees: A case study of Camellia oleifera - Xie, Haoxing; Zhang, Jian; Cheng, Junyong; Zhao, Songzi; Wen, Qiang; Kong, Ping; Zhao, Yao; Xiang, Xiaoguo; Rong, Jun (Frontiers in Plant Science, 2023)
The molecular mechanisms of freezing tolerance are unresolved in the perennial trees that can survive under much lower freezing temperatures than annual herbs. Since natural conditions involve many factors and temperature usually cannot be controlled, field experiments alone cannot directly identify the effects of freezing stress. Lab experiments are insufficient for trees to complete cold acclimation and cannot reflect natural freezing-stress responses. In this study, a new method was proposed using field plus lab experiments to identify freezing tolerance and associated genes in subtropical evergreen broadleaf trees using Camellia oleifera as a case. Cultivated C. oleifera is the dominant woody oil crop in China. Wild C. oleifera at the high-elevation site in Lu Mountain could survive below −30°C, providing a valuable genetic resource for the breeding of freezing tolerance. In the field experiment, air temperature was monitored from autumn to winter on wild C. oleifera at the high-elevation site in Lu Mountain. Leave samples were taken from wild C. oleifera before cold acclimation, during cold acclimation and under freezing temperature. Leaf transcriptome analyses indicated that the gene functions and expression patterns were very different during cold acclimation and under freezing temperature. In the lab experiments, leave samples from wild C. oleifera after cold acclimation were placed under −10°C in climate chambers. A cultivated C. oleifera variety ‘Ganwu 1’ was used as a control. According to relative conductivity changes of leaves, wild C. oleifera showed more freezing-tolerant than cultivated C. oleifera. Leaf transcriptome analyses showed that the gene expression patterns were very different between wild and cultivated C. oleifera in the lab experiment. Combing transcriptome results in both of the field and lab experiments, the common genes associated with freezing-stress responses were identified. Key genes of the flg22, Ca2+ and gibberellin signal transduction pathways and the lignin biosynthesis pathway may be involved in the freezing-stress responses. Most of the genes had the highest expression levels under freezing temperature in the field experiment and showed higher expression in wild C. oleifera with stronger freezing tolerance in the lab experiment. Our study may help identify freezing tolerance and underlying molecular mechanisms in trees.